Optimasi Tween 80 dan PEG 400 dalam Self Nanoemulsifying Drug Delivery System Antibakteri dari Minyak Daun Kemangi - Andriyani, Novia; Nurahmanto, Dwi; Kumala Sari, Lusia Oktora Ruma (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Basil has antibacterial activity against Salmonella typhi with essential oils as active compounds. However, its volatile and hydrophobic nature makes it difficult to dissolve in the gastrointestinal tract so a self nanoemulsifying drug delivery system (SNEDDS) is needed. The study aimed to determine the effect of changes in the concentration and interaction of Tween 80 and PEG 400 on the percent transmittance response and emulsification time in SNEDDS of basil leaf oil. This research optimized of Tween 80 and PEG 400 using basil leaf oil as the oil phase with the percent transmittance response and emulsification time, then verified, characterized the organoleptic, pH, particle size, size distribution, and antibacterial activity. The concentration of Tween 80 and of PEG 400 would increase the percent transmittance and decrease the emulsification time. The interaction between two substances can decrease the percent transmittance and increase the emulsification time. The prediction software design expert 11 SNEDDS optimum formula namely Tween 80 2.05 ml and PEG 400 1.35 ml. The characteristics of the optimum formula produced were clear yellow with a distinctive basil aroma, pH 6.93±0.02, particle size 183.3±0.21 nm, and PI 0.341±0.02. SNEDDS of basil leaf oil inhibits S. typhi with an inhibition zone of 19.22 ± 0.01 mm.